A theory and outcome evaluation of the South African Allan Gray Orbis Foundation (AGOF) scholarship programme from 2018 to 2023 - Thanjan, Shari (Accounting and Accountability in Africa, 2026)
The need for entrepreneurship education programmes is critical in the South African context where youth struggle with many socio-economic challenges including poverty, high youth unemployment, wealth inequality, limited access to quality education, and intergenerational poverty cycles. These programmes aim to develop entrepreneurial competencies and mindsets among young people so that they can become agents of social transformation and economic development. The following dissertation presents the findings of a theory and outcome evaluation conducted for the Allan Gray Orbis Foundation (AGOF) Scholarship Programme, an entrepreneurship education initiative targeting academically outstanding Grade 6 learners from underprivileged backgrounds in South Africa from 2018 to 2023. Two complementary evaluations were performed, namely programme theory evaluation and outcome evaluation using the Success Case Method. A combination of qualitative research methods including systematic literature review, stakeholder interviews, and semi-structured interviews with programme participants were utilised to answer the evaluation questions posed. Overall, the findings indicate that: a) the programme theory of the AGOF Scholarship Programme is consistent with best practices in entrepreneurship education and the causal logic linking programme activities to intended outcomes was deemed plausible; b) programme participants demonstrated high retention rates and developed strong entrepreneurial intentions; c) the programme was implemented effectively with comprehensive financial support, holistic coaching relationships, and quality educational placements; and d) both success and non-success participants benefited from the programme, with non-success primarily attributed to study field choices rather than programme failure. While the evaluation yielded positive results, the evaluator was able to make a number of recommendations including developing stage-specific logic models, enhancing multilingual outreach strategies, implementing offline application alternatives, and incorporating self- efficacy as a measurable outcome to improve the AGOF Scholarship Programme. This study contributes to limited research on theory-driven evaluations of adolescent entrepreneurship education programmes in developing countries and informs policy and practice in youth entrepreneurship development initiatives.